Optimizing data rate and power in BLE network for health care. Issue 6 (July 2021) - Jayanthy, S; Gouthamm, G
Abstract: There is a need for low power high bandwidth connected patient monitoring solution for patients in large volumes with easy deployment. The paper proposes data compression algorithms for optimizing data rate and power in Bluetooth Low energy network. The system is implemented using Bluetooth Low Energy (BLE) devices for data collection from a patient and a gateway to transfer the data to remote computer in an Internet Protocol (IP) network. The compression algorithms are optimized for the ARM microprocessor to compress the recorded values along with time stamps into a block. The sensor module is designed to be wearable continuously reads temperature and Electrocardiogram (ECG) and transmits them to a nearby gateway device. The gateway decompresses the data and uploads them to a cloud infrastructure. The system also allows for intensive monitoring of patient vitals. The collected data is processed and displayed in a moving graph in a remote web terminal. Results indicate that data rate and power has reduced by more than 45% and 3% respectively. With these results it is shown that high bandwidth monitoring solution is feasible with no extra expense in power. This system would be very beneficial to society in terms of affordable medical care as it can be used in large hospitals and remote medical camps alike where the patients can be monitored remotely.